Constraints on dynamic stability during forward, backward and lateral locomotion in skilled football players - Mehdizadeh, S.; Arshi, A. R.; Davids, K. (European Journal of Sport Science, 2016)
The aim of this study was to investigate effects of speed and plane of motion on stability during locomotion in skilled football players. Ten male national-level football players participated in this study to run forward, backward and in lateral directions on a treadmill at 80%, 100% and 120% of their preferred running speeds. The coordinate data of passive reflective markers attached to body segments were recorded using motion capture systems. Time series data obtained from the ankle marker were used for further analyses. The largest finite-time Lyapunov exponent and maximum Floquet multiplier were adopted to quantify local and orbital dynamic stabilities, respectively. Results showed that speed did not significantly change local and orbital dynamic stabilities in any of running patterns. However, both local and orbital dynamic stability were significantly higher in the secondary plane of progression. Data revealed that in running, unlike walking, stability in the direction perpendicular to the direction of running is significantly higher, implying that less active control is required in the secondary plane of progression. The results of this study could be useful in sports training and rehabilitation programmes where development of fundamental exercise programmes that challenge both speed and the ability to maintain stability might produce a tangible enhancement of athletic skill level.